2000
DOI: 10.2527/2000.784966x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of optimal ranges in ribeye area for portion cutting of beef steaks.

Abstract: Restaurant-ready (21-d aged, needle tenderized) loin steaks (strip, S; and T-bone, TB) representing three portion sizes (227, 284, and 340 g for S; 397, 454, and 510 g for TB) were portioned from 71 low-Choice beef carcasses representing seven ribeye size groups (70.9 cm2 and less to 103.2 cm2 and greater, in 6.3-cm2 increments). Steaks (n = 568) were cooked on a grooved grill to temperatures of either 67 or 77 degrees C and evaluated for cooking characteristics, sensory attributes (n = 284), and shear force (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Results revealed that the thickness of steaks was a significant factor (P = 0.01) influencing ESCT of a particular steak cut. These results are similar to those obtained by Gill et al (2013) and Dunn et al (2000), where the cooking times for different steak cuts were dependent on the thickness of the steak. However, in the current study, certain steak cuts (strip loin and flap) with the same thickness, but varying weights, showed significant differences (P < 0.01) in their ESCT (Table 2d).…”
Section: Experimental Safe Cooking Timessupporting
confidence: 90%
“…Results revealed that the thickness of steaks was a significant factor (P = 0.01) influencing ESCT of a particular steak cut. These results are similar to those obtained by Gill et al (2013) and Dunn et al (2000), where the cooking times for different steak cuts were dependent on the thickness of the steak. However, in the current study, certain steak cuts (strip loin and flap) with the same thickness, but varying weights, showed significant differences (P < 0.01) in their ESCT (Table 2d).…”
Section: Experimental Safe Cooking Timessupporting
confidence: 90%
“…As hot carcass weight (HCW) and ribeye area (REA) increase, steak thickness decrease in order to maintain portion size of rib and loin steaks (Dunn et al, 2000;. Bass et al (2009) found that ribeye area does not accurately predict the size and dimensions (and ultimately portion size) of many muscles in the beef carcass.…”
Section: Beef Alternative Merchandising Cutsmentioning
confidence: 99%
“…Dunn et al (2000) investigated optimum ribeye area for portion cutting of beef steaks for foodservice. This study found that thicker steaks required increased cooking times and ranked more tender (sensory panel and shear force values) with a more intense beef flavor (sensory panel) (Dunn et al, 2000).…”
Section: Beef Alternative Merchandising Cutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher-priced steaks are processed from this area of the carcass. For satisfactory cooking and eating, steaks need to have at least a minimum thickness; 12 to 15 square inches is the recommended area if the ribeye is to yield 8-to 12-ounce steaks 1 inch thick (Dunn et al 2000). If the ribeye area is too large, steaks cut to the desired thickness will be too large and too expensive, and steaks cut to the desired weight will be too thin.…”
Section: Ribeye Areamentioning
confidence: 99%